The impact of green technologies on GDP and employment in the EU - Francesca Guadagno; Oliver Reiter; Robert Stehrer (The Vienna Institute for International Economic Studies (wiiw), 2024)
Increasing production of green technologies in the EU holds great potential for the European economy. This study uses trade data and input-output tables to estimate the impacts on GDP and employment of reshoring to the EU the production of five major green technologies: photovoltaics, wind turbines, batteries, electric motors and electric vehicles. Our findings show that reshoring these five technologies would increase EU GDP by EUR 18.4 billion, or 0.13% of EU GDP, and create 242,728 new jobs. The same shift of imports to EU production would have had roughly half of the impact in 2010. We also find significant spillover effects on other sectors of the economy, particularly for metal products, wholesale and retail, professional, scientific and technical activities, and administrative and support services. To make the most from the transition, we argue that EU green industrial policy should put more emphasis on manufacturing capacities and innovation to meet the targets of the Net Zero Industry Act, remain internationally competitive, and reduce strategic dependencies.
Keywords: Q55; Q56; F14; O25; 330; green transition; photovoltaics; batteries; electric vehicles; GDP; employment